Interleukin-1B (-511) gene polymorphism is associated with acute coronary syndrome in the Turkish population - ARMAN, AHMET; ÇOKER GÜRKAN, AJDA (JOHN LIBBEY EUROTEXT LTD, 2008)
Objectives: acute coronary syndrome (ACS) is defined as an inflammatory disease associated with development of atherosclerosis and instability. IL-1 is a candidate inflammatory cytokine that is thought to trigger ACS. The purpose of this study was to determine the relationship between IL-1 gene family polymorphisms (IL-1RN, IL-1B in positions -511 and +3953) and ACS in the Turkish population. Methods: a total of 381 people participated in the study, with 117 control subjects and 264 ACS patients. Of the 264 ACS patients, 112 were diagnosed with stable angina pectoris (SAP) and 152 were diagnosed with unstable angina pectoris (USAP). The polymerase chain reaction (PCR) was used to determine the genotype of IL-1RN. The genotypes of IL-1B (-511 and +3953) were determined by PCR, followed by restriction enzyme digestion of the PCR products. Results: there were no significant differences in both IL-1RN, IL-1B (-511 and +3953) genotype distributions and IL-1RN allele frequencies between ACS patients and the control subjects. In addition, no association was observed in the allele frequency of IL-1B (-511 and +3953) between ACS patients and controls (p = 0.113 and p = 0.859, respectively), or between SAP patients and controls (p = 0.575 and p = 0.359, respectively). However, IL-1B allele 1 (C) (-511) polymorphism in USAP patients was found to be significantly different from that of control subjects (p = 0.041, OR: 2.01; 95% CI: 1.985-3.933). A significant difference was also observed between USAP and SAP patients for IL-1B (+3953) allele 1 (C) polymorphism; (p = 0.043, OR: 1.522; 95% CI: 1.012-2.88). Conclusion: these results show that IL-1RN gene polymorphism has no association with ACS. However, the allele 1 (C) of IL-1B (-511) may be a risk factor for susceptibility to USAP in the Turkish population.
Keywords: interleukin-1B; interleukin-1 receptor antagonist; polymorphism; acute coronary syndrome; RECEPTOR ANTAGONIST GENE; REACTIVE PROTEIN-LEVELS; ARTERY-DISEASE; CLUSTER POLYMORPHISMS; RHEUMATOID-ARTHRITIS; TANDEM REPEAT; PLASMA-LEVELS; IL-1; INTRON-2; ATHEROSCLEROSIS